Press History Framework for A Press History Course - Febbrizal, F; Abdurakhman, A (Proceedings International Conference on Education Innovation and Social Science, 2023)
The study of press history is a subsection of universal history that is studied and used as a patron in writing and teaching history. The study of press history is not only thematic and refers to the methodological part of research (as a primary source) but also has a unique performance to be taught at the college level and below. The research method used in this book is a literature study; the first part is collecting press history sources; the second is sorting and selecting press history; and the third is reviewing and analyzing the container that becomes the framework of Indonesian press history. This research found a suitable platform in the authorship, what is referred to as the "Indonesian Press History Framework for Press History Course," in the platform "Sejarah awal pers dan kebangkitan kesadaran keIndonesiaan, 1855–1913" by Ahmat Adam, "Jurnalisme dan politik di Indonesia: Biografi Kritis Mochtar Lubis (1922–2004) Sebagai Perenungan Redaksi dan Pengarang" by David T. Hill, and "Pers Perlawananananan: Politik Wacana Antikolonialisme Pertja Selatan" by Basilius Triharyanto.